Geotoxicology as a vector of sanitary and epidemiological wellbeing of regions - S. P. Yakutseni; R. A. Askarov (Известия высших учебных заведений: Геология и разведка)
Background. The data obtained earlier by the authors were used to classify geotoxicological risk factors into natural and anthropogenic, which contributes to ensuring environmental safety and sanitary and epidemiological wellbeing of the population. Aim. Study of geotoxicological risk factors and substantiation of their classification into natural and anthropogenic factors. Materials and methods. The materials collected during the authors’ field, chemical, and biological studies in the middle reaches of the Pechora River and the Opole Voivodeship, Poland, were used.   The research methodology was based on observational, experimental, and theoretical analyses followed by generalization of the obtained materials. Results. A methodological approach to determining the similarities and differences of geotoxicological situations in different regions, along with their temporal changes, is proposed. This approach allows identification of the key anthropogenic or natural processes that increase geoecological risks. Conclusion. The proposed approach can be used to determine not only the similarities and differences of geotoxicological situations in different regions and their changes over time, but also to identify key anthropogenic or natural processes that transfer potentially toxic elements to the active phase, increasing the exposure risks of population and the environment.